Smokeless Tobacco (SLT) Use in Delhi after Three Years of Ban on Gutka and One Year on All SLT Products - Gaurav Kumar; Pradeep Kumar (Medsci Publications, 2018)
Introduction: In September 2012, State of Delhi banned Gutka and Pan Masala containing tobacco and/or nicotine. Revised notifica- tion in March 2015 banned all smokeless tobacco (SLT) products including twin-pack. This study assesses SLT use among males in urban Delhi after three years of ban on gutka and after one year of revised ban encompassing all SLT products. Methods: Cross-sectional household survey was conducted during March-December, 2016 in urban Delhi. 1710 Households were se- lected through three-stage sampling process. One randomly se- lected adult male in each household was interviewed with stan- dardized questionnaire. Results: 25.6% adult males in urban Delhi currently use some SLT product. 7.1 % among them also smoke concurrently. Twin-pack, khaini, betel-quid with tobacco and gul are commonly used SLT products with 14.3%, 11.0%, 1.9% and 1.0% prevalence respec- tively. Two respondents consumed gutka, but procured it from Bi- har due to unavailability in Delhi. Users of other SLT products could purchase their product in Delhi. Conclusion: SLT consumption continues in urban Delhi with twin- pack and khaini being most popular products. Despite revised 2015 notification, enforcement of ban on all SLT products is limited to Gutka. Reasons for selective enforcement must be investigated and addressed for desired success in minimizing SLT consump- tion.